Differences in Self-Control of Male and Female Students in Social Interactions - Merisa Zahra; Daharnis Daharnis (Universitas Negeri Padang, 2020)
For adolescents, the need for greater interaction with peers. Peer interaction in adolescence also impacts development in later years. One of the tasks of adolescent development is to strengthen self control (the ability to control oneself). Individuals with good self control are able to control themselves in interacting with other individuals. High or low self-control can be seen from three aspects, namely (1) behavioral control, (2) cognitive control, and (3) decision control. This study aims to describe the self-control of men and women in social interactions, and examine the differences in self-control in social interactions between male and female students. This research uses comparative quantitative descriptive research methods. The sample of the research is 207 Pertiwi 1 Padang students. The instrument used was a questionnaire using a Likert scale model. The data is processed using descriptive statistical techniques and to test the difference in levels the t-test formula is used using the SPSS 16.0 application. The research findings show that: (1) the overall level of self-control of male students in social interaction is in the high category, (2) the level of self-control of female students in social interaction is in the high category, (3) there is a significant difference between controls self male students with female students in social interactions that is self control of female students higher than male students.